Stock selection via FA and TA in the semiconductor industry SGX - Ho, Andrea (2018)
The stock exchange SGX offers many different industry stocks that are for sale to the public. The main issue is how do we decide what kind and which stocks will rake in the highest returns for the investors. Before making such choices, investors can use both fundamental analysis and technical analysis. Fundamental analysis enables us to analyse the security and determine the company’s real value [1]. This is accomplished by listing out possible reasons for the fluctuation in stock prices. A few reasons are the stock market’s overall outlook during the period of purchase, their profit margin and Net income. Such analysis will give a clearer image of the company’s future potential in development and progression. It results in better indications on which securities investors should consider purchasing. Technical analysis is based on historical data that compromises of the company’s stock price and volume which can go back as early as the listed price and volume of the equity. The aim of such a method is to determine when is a relatively good time to trade in the open market. It is made up of chart patterns and technical indicators. This method may not be suited for everyone as targets short traders who observe charts on a regular basis. Both fundamental analysis and technical analysis are considered reliable in helping to deliberate investment choices. Despite the availability of both types of analysis in the market, trading could still yield less than ideal results due to the presence of human emotion. Thus, the development of various trading software to keep our emotions at bay. We must acknowledge that there are also risks in using such systems as they are also unable to predict the volatility of markets. Hence, it is ideal of investors to utilize both methods and integrating them into our investment strategy and leveraging on their plus points to yield a higher rate of return.